COLLABORATIVE GOVERNANCE IN DRUG PREVENTION BETWEEN THE NATIONAL NARCOTICS AGENCY OF PEKANBARU CITY AND THE PEKANBARU CLASS II SPECIAL CHILDREN'S DEVELOPMENT INSTITUTION - Nanda Maysarah; Rody Wahyudi (Jurnal EL-RIYASAH, 2023)
Prevention of narcotics abuse and rehabilitation of narcotics abuse victims is an important issue in various countries, including in Pekanbaru City. In an effort to overcome this problem, collaboration between the Pekanbaru City National Narcotics Agency (BNN) and the Pekanbaru Class II Special Development Institute for Children (LPKA) is a significant approach. The aim of this research is to find out the collaboration process carried out between the two parties, and then find out what the impacts of this collaboration are. The method used in this research is descriptive research with qualitative data analysis. Data collection techniques use interview, observation, documentation and literature study methods. The results of this research show that the collaboration carried out between BNNK Pekanbaru and LPKA Class II Pekanbaru has so far succeeded in changing the mindset and lifestyle habits of assisted children in prison, they have a better understanding of the dangers of drugs for their lives and future. Apart from changing their mindset and lifestyle, this collaboration was also carried out to prevent them from doing the same thing a second time after leaving prison. This was quite successful because there were no inmates who returned after being released from the rehabilitation period at LPKA Class II.